Efficacy of precutting endoscopic mucosal resection with full or partial circumferential incision using a snare tip for difficult colorectal lesions - Yoshida, Naohisa; Inoue, Ken; Dohi, Osamu; Yasuda, Ritsu; Hirose, Ryohei; Naito, Yuji; Murakami, Takaaki; Ogiso, Kiyoshi; Inada, Yutaka; Inagaki, Yoshikazu; Morinaga, Yukiko; Kishimoto, Mitsuo; Itoh, Yoshito (Endoscopy, 2019)
Background We analyzed the efficacy of precutting endoscopic mucosal resection (EMR), which is a method of making a full or partial circumferential mucosal incision around a tumor with a snare tip for en bloc resection.Methods We reviewed cases from 2011 to 2018 in which precutting EMR (n = 167) and standard EMR (n = 557) were performed for lesions of 10 – 30 mm. Precutting EMR was indicated for benign lesions of 20 – 30 mm or lesions of < 20 mm for which standard EMR was difficult. Through propensity score matching of the two groups, the therapeutic outcomes for 35 lesions of ≥ 20 mm and 98 lesions of < 20 mm in each group were analyzed.Results In the two sizes of lesion, there were significant differences between the precutting and standard groups in the en bloc resection rate (≥ 20 mm 88.6 % vs. 48.5 %, P < 0.001; < 20 mm 98.0 % vs. 85.7 %, P = 0.004) and the histological complete resection rate (≥ 20 mm 71.4 % vs. 42.9 %, P = 0.02; < 20 mm 87.8 % vs. 67.3 %, P < 0.001).Conclusion Precutting EMR enabled high en bloc resection rates in cases involving difficult lesions.